Simplify Boolean Expression A’B’C + A’BC + AB’C

boolean-algebra

The K-map method of simplifying the Boolean Expression A'B'C + A'BC + AB'C gives the answer to be A'C+B'C. But I am not able to solve this algebraically. Please help me out.
What I have tried is

A'B'C + A'BC + AB'C
= A'C (B'+B) + AB'C
= A'C(1) + AB'C
= A'C + AB'C

This is the most simplified I get using Boolean algebra but this is not matching the result. Can someone please help me out.

Best Answer

With the use of A+A=A we have

$$ A'B'C + A'BC + AB'C =\\ = \underbrace{\color{blue}{A'B'C} + A'BC} +\underbrace{\color{blue}{A'B'C}+ AB'C}=\\ =A'C (B'+B) + (A+A')B'C $$

Related Question